Regulation of inflammatory response to polyglycolic acid scaffolds through incorporation of sodium tripolyphosphate. (5th January 2020) - Zhang, Jiapeng; Song, Chaobo; Han, Yuqing; Xi, Zhenhao; Zhao, Ling; Cen, Lian; Yang, Ying
Graphical abstract: Highlights: Sodium tripolyphosphate was added into PGA scaffolds as fillers via CO2 foaming. The effects of PGA on the expression of macrophages when pH = 3.6 was explored. IL-10 with a similar in vitro and in vivo trend could be used as an indicator. PGA-TPP implants relived inflammation and improved phagocytosis in a porcine model. The pro-healing macrophages were only found in PGA-TPP implants post-surgery. Abstract: Polyglycolic acid (PGA) is a typical polyester with successful clinical and commercial applications. It causes severe host response and needs modification according to clinical cases. The expression of the pro-healing cytokine, IL-10, from macrophages as indicators of immune-response to PGA medical devices can be the key to be revealed. We thereby intended to modify PGA to affect its degradation profile and modulate the secretion of cytokines by macrophages. Sodium tripolyphosphate (TPP) was incorporated into PGA scaffolds as fillers via a scCO2 foaming process. A porcine subcutaneous model was further employed to evaluate the inflammation and the expression profiles of macrophages (IL-10 and IL-1β as well as their phenotypes) in these implants. It was shown that IL-1β and IL-6 were both inhibited in vitro in PGA and PGA-TPP groups without dependence on pH. The secretion of TNF-α was stimulated when pH was 6.1 and was inhibited by acidosis with pH of 3.6. IL-10 was also suppressed when pH was 3.6. In vivo expression of IL-1β was increased in both groups. However, IL-10 exhibited higher values in PGA-TPP group than in PGA one, although a decreasing trend appeared in PGA-TPP implants from the 2nd to the 4th week. The infiltration of leukocytes was still severe in PGA scaffolds after two weeks post-surgery, while this was evidently relieved in PGA-TPP ones. In summary, the incorporation of TPP into PGA implants could be an efficient way to relief the inflammatory response and to improve the clinical outcomes of translational polyester implants.